National wetland inventory mapping of the Arkansas Headwaters Subbasin - Lemly, Joanna, author; Long, Lexine, author; Smith, Gabrielle, author; Sueltenfuss, Jeremy, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2016)
Wetlands are an integral component of Colorado's landscape and provide a host of beneficial services, such as wildlife habitat, flood abatement, storm water retention, groundwater recharge, and water quality improvement. Wetlands and riparian areas in the Arkansas Headwaters subbasin support biologically significant resources, including plants animals and natural communities. Decisions about wetland management should be based on a solid understanding of their extent and distribution. Yet for most of Colorado, including the Arkansas Headwaters subbasin, these data have historically been lacking because National Wetland Inventory (NWI) mapping by the U.S. Fish and Wildlife Service was available only on paper. The goal of this project was to create an up-to-date digital map of wetlands in the Arkansas Headwaters subbasin to aid regulatory, conservation and management decisions. The first step was to digitize original 1970–80s NWI maps for areas of the basin lacking digital data. The second step was to create new, updated NWI maps for the subbasin. The last step was to compare the historical and contemporary mapping to evaluate trends in the extent and type of aquatic resources. From this analysis, we attempted to qualitatively distinguish what changes in the mapping represented true changes in the landscape and what changes came from updated mapping methodologies. … Through the NWI mapping and field excursions to the area, it is clear that water development projects over the past 100 years have had a profound and lasting impact on the wetland and aquatic resources of the Arkansas subbasin. With increasing population growth forecasted for the larger Arkansas Basin and the Front Range, and the potential for a warming and drying climate, action should be taken to conserve the important wetland resources of the Arkansas Headwaters subbasin.
Prepared for: EPA Region 8 Wetlands Program.
March 2016.